2020
DOI: 10.1111/nph.16387
|View full text |Cite
|
Sign up to set email alerts
|

Variation for heterodimerization and nuclear localization among known and novel oil palm SHELL alleles

Abstract: Summary Oil palm breeding involves crossing dura and pisifera palms to produce tenera progeny with greatly improved oil yield. Oil yield is controlled by variant alleles of a type II MADS‐box gene, SHELL, that impact the presence and thickness of the endocarp, or shell, surrounding the fruit kernel. We identified six novel SHELL alleles in noncommercial African germplasm populations from the Malaysian Palm Oil Board. These populations provide extensive diversity to harness genetic, mechanistic and phenotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…It has been proposed that different fruit forms in oil palm are controlled by SHELL , a type II MADS-box gene that controls ovule identity and seed development in Arabidopsis ( Singh et al, 2013 , 2020 ). More so, MADS-box genes have a role in pollen fertilization and the development of seedless fruits ( Klap et al, 2017 ; Takisawa et al, 2018 ; Tang et al, 2019 ; Wei et al, 2019 ; Molesini et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that different fruit forms in oil palm are controlled by SHELL , a type II MADS-box gene that controls ovule identity and seed development in Arabidopsis ( Singh et al, 2013 , 2020 ). More so, MADS-box genes have a role in pollen fertilization and the development of seedless fruits ( Klap et al, 2017 ; Takisawa et al, 2018 ; Tang et al, 2019 ; Wei et al, 2019 ; Molesini et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… Singh et al (2013) reported that SHELL gene is responsible for endocarp development, which differentiates three fruit forms: Dura, Tenera, and Pisifera in oil palm. The authors found two independent mutations in MADS-box transcription factor SHELL , a homolog of the MADS-box gene SEEDSTICK (also known as AGAMOUS-Like 11, AGL11 ), which acts on the ovule identity and seed development in Arabidopsis ( Singh et al, 2013 , 2020 ). In addition, MADS-box genes have also been reported to be implicated in pollen fertilization and the development of seedless fruits ( Klap et al, 2017 ; Takisawa et al, 2018 ; Tang et al, 2019 ; Wei et al, 2019 ; Molesini et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The variation in total amounts of FAPE and FAGGE in the kernel was low as compared to the mesocarp where the contents of FAPE and FAGGE varied by a factor of two compared to the control line Deli x La Mé. It has been shown that the variation for a given trait in a population is maximal for the population where the highest genetic variation is expected, that is usually the place of its origin (Singh et al, 2020). Indeed, Oil Palms have been used by humans for several thousand years in the region of its origin in West Africa, but commercial cultivation of elite lines started in East Asia only about 100 years ago (Sambanthamurthi, 2000).…”
Section: Natural Variation Of Fape and Fagge Contents In African Oil mentioning
confidence: 99%
“…Advances in molecular technology were allowed the molecular studies of the flowering genes that play a role in flowering (Santos et al 2020;Uguru et al 2020). In most plants, the flowering process is controlled by many genes, such as SQUA, AGL, GLO, AG, and DEF genes that are mutually reliable (Singh et al 2020). The structural character from E. guineensis to the MADS-box genes, namely SQUAMOSA, DEFICIENS, GLOBOSA, AGAMOUS, and AGL2 subfamily (Adam et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…On oil palm, the molecular development of flowers is still limited. Singh et al (2020) have been reported oil yield was controlled alleles type II MADS-box genes (SHELL) to impact of presence that thickness from endocarp, shell, and fruit of kernel. Recently, Li et al (2020) have been reported EgMADS21 was expressed to early mesocarp development stages from oil palm fruits to a negative correlation.…”
Section: Introductionmentioning
confidence: 99%